PERILAKU IBU HAMIL DENGAN PRE EKLAMPSI DALAM UPAYA PENCARIAN PERTOLONGAN KESEHATAN DI RUMAH SAKIT - Erna Widyastuti (JURNAL KEBIDANAN, 2015)
Maternal Mortality Rate (MMR) in Indonesia is the highest in ASEAN. The maternal mortality rate (MMR) can be used as one indicator of public welfare, especially maternal health indicators with a target of 2015 MMR pressed until the number 102 per 100.000 live births. This research is qualitative research. Data was collected in triangulation, data analysis is inductive. The study population of pregnant women with pre-eclampsia.            Research subjects pregnant women with pre-eclampsia in the general hospital Semarang. Data were collected by in-depth interview techniques. Processing and analysis of data using content analysis.            The results showed that a history of behavior: 1) of the ANC's behavior in accordance with a standard that is at least four times. Pre-eclampsia detected in the third trimester of pregnancy at the age of 8-9 months. 2) Behavior diet during pregnancy is still health qualify because there is no prohibition to eat 3) Behavior patterns of daily activity is working in a factory so there is a double burden of household and help make a living; 4) The behavior of respondents lifestyle there is not a healthy behavior to follow pregnancy exercise for reasons no time; 5) Behavior efforts in the health seeking diligently check the ANC and agree referenced when detected pre eclampsia. Midwife should be advised early detection, emphasizing visit once a week in third trimester and provide health education to pregnant women and families  about preeclampsia.